Rice husk hydrochars from metal chloride-assisted hydrothermal carbonization as biosorbents of organics from aqueous solution - Yin Li; Fana Mulugeta Hagos; Rongrong Chen; Hanxin Qian; Chengxing Mo; Jing Di; Xikun Gai; Ruiqin Yang; Genxing Pan; Shengdao Shan (Bioresources and Bioprocessing, 2021)
Abstract Hydrochar a carbon-rich material resulting from hydrothermal carbonization of biomass, has received substantial attention because of its potential application in various areas such as carbon sequestration, bioenergy production and environmental amelioration. A series of hydrochars were prepared by metal chloride-assisted hydrothermal carbonization of rice husk and characterized by elemental analysis, zeta potential, X-ray diffraction, Brunauer–Emmett–Teller measurements, Fourier transform infrared spectroscopy, thermogravimetric analysis, X-ray photoelectron spectroscopy and scanning electron microscopy. The results reveal that the prepared hydrochars have carbon contents ranging from 45.01 to 58.71%, BET specific areas between 13.23 and 45.97 m2/g, and rich O-containing functional groups on the surfaces. The metal chlorides added in the feedwater could improve the degree of carbonization and show significant effects on the physical, chemical and adsorption properties of the hydrochars. The adsorption of the selected organics on the hydrochars is a spontaneous and physisorption-dominated process. The hydrochars possess larger adsorption capacities for 2-naphthol than for berberine hydrochloride and Congo red, and the modeling maximum adsorption capacities of 2-naphthol are in the range of 170.1–2680 mg/g. The adsorption equilibrium could be accomplished in 10, 40 and 30 min for 2-naphthol, berberine hydrochloride and Congo red, respectively. These results suggest metal chloride-assisted hydrothermal carbonization a promising method for converting biomass waste into effective adsorbents for wastewater treatment.